Synthesis and Evaluation of Triphenylphosphonium- Pluronic F127 Conjugate for Enhanced Mitochondrial Targeting in Drug Delivery Systems - Katrolia, Archita; Singh, Rohit; Shukla, Vikesh Kumar (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Mitochondria, often termed the "powerhouse of the cell", have increasingly become a focal point for the targeted delivery of therapeutic agents in the treatment of various metabolic disorders. This emerging field, known as mitochondrial medicine, emphasizes recognition of mitochondria as a critical target for the delivery of therapeutic agents aimed at addressing metabolic dysfunctions. Triphenylphosphonium (TPP) is the most utilized mitochondrial targeting moiety. It is a delocalized cationic lipid that efficiently accumulates within and traverses the mitochondrial membrane, driven by the strongly negative mitochondrial membrane potential. On the other hand, Pluronic F127 (PF127), a triblock copolymer known for its high Hydrophilic-Lipophilic Balance (HLB) value, demonstrates limited affinity for cellular membrane interactions. Materials and Methods: The conjugation of TPP with PF127 alters the physicochemical properties of the resulting polymeric micelles, reducing the HLB value and enhancing the interaction with cellular membranes. This modification enables the formation of micelles capable of delivering therapeutic moieties specifically to mitochondria, thereby significantly improving their bioavailability and therapeutic index. This study aims to synthesize the TPP-PF127 conjugate (TP) and subsequently characterize it using Fourier-Transform Infrared (FT-IR) Spectroscopy. Results: The characterization data confirmed the successful conjugation of TPP and PF127. Conclusion: Furthermore, the findings from confocal microscopy further support the efficacy of the conjugate in specifically targeting mitochondria, underscoring its promise in the development of mitochondrial-targeted therapeutic strategies.
Keywords: Mitochondrial Medicine; Triphenylphosphonium; Pluronic F127; Conjugate; Mitochondrial Targeting